Investigations on secondary metabolites from crateva religiosa G. Forst.–a rare medicinal plant of Vidarbha region (m.s.) India - WAGAY N. A., (International Journal of Pharma and Bio Sciences, 2017)
Crateva religiosa G. Forst. is commonly called as ‘Viawarna’ belongs to family Capparaceae which is used as folkloric medicine to cure various types of ailments. In the present study, the roots of this plant were extracted successively in three different solvents, Chlorofrom, Dichloromethane and 50% Ethanol by soxhletion method. Gas Chromatography – Mass Spectrometry (GC-MS) method was used to separate and identify the individual compounds in all the three extracts. The compounds were identified by comparing mass spectra of the separated compounds with those in the NIST library. Fifteen important secondary metabolites were identified in the roots of this plant which were having several biological activities thereby verifying the folkloric claims of this plant part.